Pengetahuan dan Sikap Mahasiswa Keperawatan Terkait Protokol Kesehatan Selama New Normal di Universitas Tanjungpura - Nadia, Priska Liz; Mita, Mita; Yulanda, Nita Arisanti (Universitas Malahayati, 2023)
ABSTRACT Limited face-to-face learning is one of the policies issued by the government in the New Normal era. This policy is done to reduce direct contact with people to prevent the spread of COVID-19. The rapid development of the virus is caused by non-compliance with health protocols so students are required to implement health protocols to suppress the spread of COVID-19. Knowledge and attitudes play an important role in compliance with the application of health protocols, so this research is needed. To analyze the relationship between students knowledge and attitudes regarding health protocols during the new normal. This research is a quantitative study with a correlational study design and a cross sectional approach. Determination of the sample using purposive sampling with 155 respondents. The analysis of this study uses the Kendall's Tau test. The characteristics of respondents consist of gender categories, age and academic year. Most of the respondents is female (86.45%), age ranged from 19-21 years (68.4%) and in the second semester of academic year (47.1%). Most of the respondents have a sufficient level of knowledge (52.26%) and most of the respondents attitudes are in the positive category (60%). The results of the correlation test obtained a p-value of 0.048 and a correlation coefficient of 0.153. There is a relationship between the level of knowledge and attitudes of students regarding health protocols. The correlation coefficient value indicates that the two variables have a weak positive relationship. This means that a sufficient level of knowledge has been able to have an impact on a positive attitude in implementing the COVID-19 health protocol. Students are expected to improve the application of health protocols, especially in the campus area. Keywords: COVID-19, Health Protocol, Knowledge, Attitude ABSTRAK Pembelajaran tatap muka terbatas menjadi salah satu kebijakan yang dikeluarkan oleh pemerintah dimasa New Normal. Hal ini dilakukan untuk mengurangi kontak langsung dengan orang-orang sehingga dapat mencegah penyebaran COVID-19. Perkembangan virus yang cepat disebabkan oleh ketidakpatuhan terhadap protokol kesehatan sehingga mahasiswa diwajibkan untuk menerapkan protokol kesehatan untuk menekan penyebaran COVID-19. Pengetahuan dan sikap berperan penting dalam kepatuhan penerapan protokol kesehatan sehingga diperlukannya penelitian ini. Menganalisis hubungan pengetahuan dan sikap mahasiswa keperawatan terkait protokol kesehatan selama new normal. Penelitian ini merupakan studi kuantitatif dengan desain studi korelasional dan pendekatan cross sectional. Penentuan sampel menggunakan purposive sampling dengan 155 responden. Analisis penelitian ini menggunakan uji Kendall’s Tau. Karakteristik responden terdiri dari kategori jenis kelamin, usia dan tahun akademik. Sebagian besar responden berjenis kelamin perempuan (86,45%), usia berada pada rentang 19-21 tahun (68,4%) dan tahun akademik semester 2 (47,1%). Sebagian besar responden memiliki tingkat pengetahuan dalam kategori cukup (52,26%) dan sebagian besar sikap responden dalam kategori positif (60%). Hasil uji korelasi diperoleh nilai p-value 0,048 dan nilai koefisien korelasi 0,153. Ada hubungan antara tingkat pengetahuan dan sikap mahasiswa terkait protokol kesehatan. Nilai koefisien korelasi menunjukkan bahwa kedua variabel tersebut memiliki hubungan positif yang lemah. Hal ini bermakna bahwa tingkat pengetahuan yang cukup sudah mampu memberikan dampak pada sikap yang positif dalam menerapkan protokol kesehatan COVID-19. Mahasiswa diharapkan dapat meningkatkan penerapan protokol kesehatan terutama di area kampus. Kata Kunci: COVID-19, Protokol Kesehatan, Pengetahuan, Sikap